JUDGING ADMINISTRATIVE JUDGES: OVERSIGHT, ACCOUNTABILITY, AND CITIZEN COMPLAINTS - Tomkinson, Sule; Brulotte, Hubert; Cormier, Dorothée; Desnoyers, Nicolas; Faye, Katy; Lanouette, Catherine; Trudel, Jérémy (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2024)
The Conseil de la justice administrative [CJA] is a distinct oversight body responsible for investigating complaints of deontological breaches committed by members of administrative tribunals in Quebec that wield quasi-judicial powers. In our examination of the CJA’s decisions, we consider it to be a crucial accountability mechanism within the Quebec administrative justice system. Our analysis focuses on identifying the complainants, the nature of their complaints, the tribunals they target, the outcomes of these complaints, and the CJA’s approach to handling them. We found that over 73 percent of the investigated complaints are filed by citizens who allege disrespectful conduct and delays in tribunal decision-making. A significant portion of investigated complaints – nearly 60 percent – are directed at judges from the Tribunal administratif du logement [TAL], the agency responsible for the largest caseload in the province. Of the complaints investigated, around 28 percent were found to involve misconduct, with the CJA recommending sanctions in over 70 percent of substantiated cases. Our analysis reveals that the CJA adopts inquisitorial and restorative approaches in handling complaints rather than an adversarial one. This strategy is focused on remedying harm, ensuring accountability, and restoring public confidence rather than solely imposing punitive measures. Our study contributes to the expanding literature on citizen complaints against public officials by providing an exploratory analysis of the oversight of Quebec’s administrative judges and the handling of complaints against them.